CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) AND BALANCED NUTRITION IN SCHOOL CHILDREN IN THE NEW NORMAL MASS - Suci Dwi Aningsih, Baharika; Kartiko Kusumo Wardani, Dyah Woro (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Covid-19 is a disease caused by a viral infection. As Covid-19 continues to spread, the government is calling on the Indonesian people to live in peace with the coronavirus by implementing 'New Normal' in all sectors while adhering to health protocols. PHBS (Clean and Healthy Lifestyle) and balanced eating are ways of adapting to new habits that not only adults but children need to adopt as well. This is because toddlers and children are a group that is vulnerable to transmission of this virus and therefore need to be able to carry out school activities while adapting to the new normal. School-age children's lack of knowledge about PHBS and a balanced diet can compromise their immunity and health. In connection with this problem, charitable activities in the form of training in proper hand washing and a balanced diet were carried out at Sint John Harapan Indah Elementary School, which had never happened at this elementary school. As knowledge grows, it is hoped to change the behavior of elementary school children so that they become better and more adaptable to the new normal. From the results of the pre- and post-tests conducted on 125 participants, there was a 96% increase in knowledge. This demonstrates that this health promotion activity succeeded in expanding knowledge and providing participants with knowledge about PHBS and balanced nutrition.